2019
DOI: 10.1002/aelm.201900668
|View full text |Cite
|
Sign up to set email alerts
|

Ionically Conductive Pastes as Conformable Collector for Transparent, Nonplanar Triboelectric Devices

Abstract: Recently, the transparency of these deformable devices has been significantly highlighted. [4-6] On the one hand, a high light transmittance contributes to visual access to information, which can be quite important for touch panels and interactive systems. [5,7] On the other hand, external light stimuli can be applied through transparent devices to their underlying objects, which is of great significance in some fields like neural imaging and optogenetic applications. [8-10] Unfortunately, existing electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In such experiments, the recovery of fluorescence intensity in the bleached zone is generally due to the interdiffusion of unbleached fluorescent polyelectrolytes from outside of the zone. , As shown in Figure C, the fluorescence recovery of (PEI/PAA) 15 films in ethanol is considerably less noticeable than that in deionized water, indicating that the interdiffusion of polyelectrolyte chains can be effectively suppressed by solvent exchange to ethanol. Since the macroscopic strength of a polymeric material can be affected by its chain mobility, ,, we further tested the mechanical properties of (PEI/PAA) 15 films in deionized water and in ethanol (Figure D). It can be found that the Young’s modulus of the films is 1030.98 ± 78.45 MPa in ethanol, which is three orders of magnitude higher than 1.81 ± 0.59 MPa in deionized water.…”
Section: Resultsmentioning
confidence: 99%
“…In such experiments, the recovery of fluorescence intensity in the bleached zone is generally due to the interdiffusion of unbleached fluorescent polyelectrolytes from outside of the zone. , As shown in Figure C, the fluorescence recovery of (PEI/PAA) 15 films in ethanol is considerably less noticeable than that in deionized water, indicating that the interdiffusion of polyelectrolyte chains can be effectively suppressed by solvent exchange to ethanol. Since the macroscopic strength of a polymeric material can be affected by its chain mobility, ,, we further tested the mechanical properties of (PEI/PAA) 15 films in deionized water and in ethanol (Figure D). It can be found that the Young’s modulus of the films is 1030.98 ± 78.45 MPa in ethanol, which is three orders of magnitude higher than 1.81 ± 0.59 MPa in deionized water.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the prepared hydrogels exhibit high transparency, with a transmittance value that is close to 92% at 650 nm wavelength (Figure S10, Supporting Information) due to the homogeneous microstructure and the multiple interactions in the conductive networks; this transmittance reaches or exceeds the advanced level when compared with the relevant references. [42][43][44] Finally, this interpenetrating and interbonding 3D network can simultaneously achieve the synergistic mechanical performance, conductivity, and multifunctionality of the PAM/PBA-IL/CNF ICH, which endows it with immense potential for use in multifunctional wearable sensors. Mechanical properties, as some of the most critical factors, play vital roles in the field of flexible sensors because remarkable mechanical strength can respond to various external applied forces, thereby providing great potential for detecting diverse deformations.…”
Section: Design and Preparation Of The Pam/pba-il/cnf Hydrogelsmentioning
confidence: 99%
“…As shown in Figure 1d, the as-prepared 3.7-mm-thick eutectogel film exhibits high transparency of up to 98% in the visible region (380-780 nm), which exceeds the advanced level compared with the relevant references. [40,41,42] Furthermore, the presence of free charge carriers from ChCl and ILs renders the high ionic conductivity to eutectogel thereby displaying multi-responsiveness to strain, temperature, and humidity. Besides, the introduction of IL is in favor of modulable mechanical and conductive performances for comfortable flexibility and high sensitivity in fields of soft electronics.…”
Section: Design Principle and Synthesis Of The Eutectogelmentioning
confidence: 99%